PL.12 Short Term Clinical Outcomes of Neonates with Severe Perinatal Acidosis: A Prospective Study. (26th April 2013) - Marthandan, A; Ramaiah, S; Shah, D; Roy, R; Clarke, P
Abstract : Background: Therapeutic hypothermia improves outcomes for asphyxiated infants, however not all infants born with severe acidosis are assessed as eligible for cooling and few data describe short-term clinical outcomes for the whole cohort of babies with severe perinatal acidosis. Aim and Methods: We conducted a prospective study over a 17-month period (June 2011-November 2012) to determine short-term clinical outcomes in the whole cohort of infants born at >35 weeks gestation who had an arterial cord or first hour pH of ≤7.10. Results: 69 infants were admitted with severe acidosis. CTG abnormalities were present in 71% of cases. Overall, 31/69 (35%) infants showed signs of hypoxic-ischaemic encephalopathy (HIE) and 12/69 (17%) were cooled. Of non-cooled infants, 8/57 (14%) developed moderate-severe HIE (Table 1 ). Conclusion: Short term morbidities are common in the whole cohort of infants born with severe perinatal acidosis, including in infants initially evaluated as not meeting current criteria for cooling.